Pedagogical relationships: A master-apprentice model in music teaching - Heald, Jody (Curtin University, 2019)
The thesis entitled Pedagogical Relationships: A master-apprentice model in music teaching is a pedagogical and phenomenological inquiry into the lived experience of the master-apprentice model of piano teaching in a private studio. It surveys the history of the instrument, its literature, its pedagogy and the importance of genealogy in this mentor-protégé relationship. Using narratives, interviews, audio-visual links, illustrations, musical score illustrations and literary references, the thesis illuminates authentic lived experiences of both teacher and student.